Upaya Memahami Riset Otopsi Psikologi - Lutviana, Zhella (Universitas Batanghari Jambi, 2025)
This study analyzes psychological autopsy research with the aim of better understanding the objectives, methods and results of the research. There are 6 cases in the study, with 5 foreign countries and 1 from Indonesia. The results of the study show that psychological autopsies conducted abroad and in Indonesia have similarities in collecting data related to victims, namely using documents related to the victim, interviews, also using clinical interviews for DSM-IV Axis I, but for DSM-IV Personality Disorders (SCID-II) clinical interviews have not been used in psychological autopsies in Indonesia. Psychological autopsy research in Indonesia is still rarely done based on a search with the keyword psychology autopsy in Indonesia only found one study related to psychological autopsy.